Post-Western histories of architecture - Guerrieri, Pilar Maria; Biraghi, Marco 1959- (Routledge, Taylor & Francis Group, 2023)
Architecture as a 'Political Act' -- A Dialogue with Tradition: the Case of Italy -- Principles of North-European Sustainability -- The Construction of the Indian Identity -- The Latin American Political Context and its Architecture -- Using the African Context -- 'Indirect' Context: the Case of Japan -- China and the Re-Invention of Tradition -- Re-embracing the Aboriginal Model: Australia -- Context as an Opportunity. A Way of Viewing Architecture.
Keywords: Geschichte 2000-2023; Politik; Klimaschutz; Gesellschaft; Architekturtheorie; Architektur; Nachhaltigkeit; Japan; Australien; Indien; Italien; Nordische Staaten; China; Lateinamerika; Architecture / History; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / History